Empowering Educators: The Principal's Strategy in Enhancing Teachers' Professional Competence in Islamic Schools - Sultan, Muh. Yahya; Thaha, Hisban; Sanusi, Syamsu (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
This study examines the strategies employed by principals in enhancing teachers' professional competence within Islamic schools. Using a qualitative descriptive approach and a case study design, data were collected through in-depth interviews, classroom observations, and document analysis. The findings reveal that principals implement structured professional development programs, mentorship and coaching initiatives, collaborative learning environments, spiritual and moral guidance, and institutional support to improve teachers' instructional skills and overall performance. The study highlights that professional development programs enhance pedagogical skills and encourage innovative teaching methods. Mentorship and coaching provide novice teachers with valuable feedback and support, leading to improved classroom management and student engagement. Collaborative learning environments, such as MGMP meetings, foster the exchange of best practices and continuous learning. Additionally, spiritual and moral guidance strengthens teachers' ethical conduct and emotional connection with students, while institutional support, including access to resources and recognition of achievements, boosts teacher motivation and job satisfaction. The results of this study align with educational theories such as Social Learning Theory, Sociocultural Theory, and Herzberg's Two-Factor Theory. However, challenges such as limited funding, resistance to change, and the need for continuous evaluation were also identified. The study concludes that the strategies implemented by principals effectively enhance teachers' professional competence by addressing both technical and moral aspects of teaching. Future research is recommended to assess the long-term impact of these strategies on student outcomes and explore the role of technology in supporting professional development.